2013
DOI: 10.1016/j.cca.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

High cortisol levels are associated with cognitive impairment no-dementia (CIND) and dementia

Abstract: The elevation in cortisol concentrations is associated with dementia, independently of APOE genotypes. Further studies are required to understand if elevation of cortisol is an initial event and how hippocampal damage and the loss of hypothalamus-pituitary-adrenal (HPA) axis inhibition may affect its concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…This may be a limitation because previous studies have suggested the modifying role of APOE-4 on the association between cortisol levels and cognition (Gerritsen et al, 2011;Lee et al, 2008). However, recent evidence does not support the modifying role of APOE-4 in this relationship (Fiocco et al, 2008;Lara et al, 2013).…”
Section: Study Strengths and Limitationsmentioning
confidence: 94%
See 1 more Smart Citation
“…This may be a limitation because previous studies have suggested the modifying role of APOE-4 on the association between cortisol levels and cognition (Gerritsen et al, 2011;Lee et al, 2008). However, recent evidence does not support the modifying role of APOE-4 in this relationship (Fiocco et al, 2008;Lara et al, 2013).…”
Section: Study Strengths and Limitationsmentioning
confidence: 94%
“…Furthermore, there are other clinical studies that examined these relationships but yielded mixed findings with most studies reporting higher morning cortisol levels. In addition, some studies focused on specific study populations, for example, among APOE-4 carriers and non-carriers (Gerritsen et al, 2011;Lara et al, 2013;Lee et al, 2008), MCI subjects (Lind et al, 2007;Venero et al, 2013), and diabetic patients (Reynolds et al, 2010). Thus, these previously mentioned studies were not generalizable to the older general population.…”
Section: Blunted Cortisol Response Is Associated With Poorer Cognitivmentioning
confidence: 99%
“…However, some studies suggested that benzodiazepines could precipitate the onset of dementia or mental decline by altering or impairing higher mental activities. Along these lines, Saczynski et al [7] mentioned that depressive symptoms were associated with an increased risk of subsequent cognitive decline, and Lara et al [29] found that high levels of cortisol may be associated with depression and stress and may thus cause neural death. Furthermore, a study reported an increased risk of stroke and coronary heart disease in patients with the ApoE polymorphism, a known genetic risk factor for dementia [30] .…”
Section: Main Findingsmentioning
confidence: 99%
“…Elevated cortisol levels have been associated with impairments in cognition [76]. Furthermore, heightened inflammation as detected by elevated circulating IL-6 levels and intracellular production of pro-inflammatory cytokines by monocytes have been linked to cognitive decline [83, 112].…”
Section: Part Iv: Isolation and Cognitive Function Dementia And Alzmentioning
confidence: 99%